Naxos of Sicily. Investigations in the classical city. The discovery of traces of an abandonment ritual (Excavations 2019) (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2024)
Una breve campagna di scavo nel 2019 ha riportato in luce i crocevia tra gli stenopoi 8 e 9 e la plateia A, principale asse viario E/O dell’impianto urbano a griglia di epoca classica. Come tutti i crocevia sinora scoperti, essi conservano presso l’angolo sud-est i resti della base quadrangolare di un altare, particolarità unica del sistema urbano di V secolo a.C. di Naxos di Sicilia. Nel crocevia A9, l’esplorazione estesa ai prospicienti blocchi di abitazioni ha individuato all’interno di un ambiente aperto sull’incrocio un deposito votivo, nel quale è possibile riconoscere le tracce di un rituale compiuto all’interno della casa in concomitanza con la distruzione della città nel 403 a.C., forse assimilabile a un rito di abbandono. A short excavation campaign in 2019 brought to light the intersections of Stenopoi 8 and 9 with Plateia A, the main E/W road axis of the city's grid system in the Classical period. Like all the intersections discovered so far, they preserve in their south-eastern corner the remains of the quadrangular base of an altar, a unique feature of the 5th century BC urban plan of Naxos in Sicily. At crossroad A9, the research, which has been extended to the adjacent blocks of houses, has revealed a votive deposit in a room in direct communication with the crossroad, in which it is possible to recognise traces of a ritual performed inside the house at the time of the destruction of the city in 403 BC, a possible abandonment ritual.
Keywords: crossroads; altar base; mug; cheese grater; libation